2020
DOI: 10.5267/j.ijdns.2020.9.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of digital transformation on the individual job performance of insurance companies in Peru

Abstract: The objective of this study was to analyze and determine the impact of digital transformation on the individual job performance of insurance companies in Peru. The deductive inferential scientific method of explanatory level was used, with a non-experimental design, to four insurance companies that operate in the regions of Arequipa, Cusco, Iquitos, Lima, Tacna and Trujillo. The results generated by structural equations show that customer service experience (CSE), based on digital transformation, had a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Chen, Jaw & Wu (2016) found that digital transformation could have a negative impact on industry benchmark information but that further investigation is required to confirm. Guzmán-Ortiz et al (2020) found that although digital transformation has a significant effect on task performance that it has little or no effect on customer's service experience. Vial (2019) reviewed that the changes brought by digital transformation could have both positive and negative outcomes.…”
Section: Digital Transformation and Its Impact On Business Performancementioning
confidence: 99%
“…Chen, Jaw & Wu (2016) found that digital transformation could have a negative impact on industry benchmark information but that further investigation is required to confirm. Guzmán-Ortiz et al (2020) found that although digital transformation has a significant effect on task performance that it has little or no effect on customer's service experience. Vial (2019) reviewed that the changes brought by digital transformation could have both positive and negative outcomes.…”
Section: Digital Transformation and Its Impact On Business Performancementioning
confidence: 99%
“…However, many customers have resistance to using digital technologies due to a lack of habits and skills. Although the interface of the apps is intuitive, companies should provide the operating instructions to customers so that they can use them with more autonomy, especially for the older population (Cobelli and Chiarini, 2020;Guzm an-Ortiz et al, 2020;Zaki, 2019). Another aspect that negatively impacts the digitalization of customer service is digital security.…”
Section: Digitalization Of Customer Service In Smesmentioning
confidence: 99%
“…With the assistance of AI, the chatbot provides more dynamic and refined service to users, simulating human dialogues that reduce the discomfort of customers talking to robots. Thus, SMEs can reduce the number of call center employees while improving the capacity for simultaneous calls (Falle et al, 2016;Guzm an-Ortiz et al, 2020;Leong et al, 2019). In addition, SMEs should use different techniques and resources to make their service more attractive, personalized, and satisfactory to their customers.…”
Section: Technologiesmentioning
confidence: 99%
“…The impact of changes in the characteristics and nature of work is the disruption of old jobs with new jobs [4], [5]. Thus, the workers have to perform updates competence to meet the challenges of the presence of new jobs [6].…”
Section: Introductionmentioning
confidence: 99%